Corporate Communication Strategy in Building Corporate Identity (A Study on RH Petrogas Company in Indonesia) - Heraziza, Dinda Prilla; Sunarto, Sunarto; Santoso, Prasetya Yoga (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to analyze how the corporate identity and corporate communication strategies of RH Petrogas contribute to building the company's image, as well as how internal and external communication influence employees' understanding of the company's identity. Employing a qualitative approach with a case study method, the research reveals that while the company's external communication strategy has successfully built a positive reputation among stakeholders, internal communication still faces challenges in disseminating a consistent understanding of the company's values and philosophy to all employee levels. The findings indicate that many employees, particularly at the operational level, have not fully grasped the deeper meaning of the company's identity elements due to the lack of effective socialization and internal communication. Therefore, this study recommends improving the internal communication strategy to be more interactive and involve various organizational layers to enhance employees' comprehension and engagement with the company's corporate identity. To address these challenges, the study suggests that RH Petrogas should invest in more robust internal communication initiatives, such as implementing interactive forums, regular town hall meetings, and tailored training programs to ensure the company's values, philosophy, and identity are consistently understood and embraced by all employees across the organization. This is crucial for ensuring all employees can understand and internalize the company's corporate identity, enabling them to contribute more effectively in building the company's positive image among stakeholders.